Analisis Pengendalian Internal Pelaporan Keuangan Guna Peningkatan Kualitas Laporan Keuangan dalam Rangka Mendukung Tugas Staf Kebijakan dan Perencanaan Umum TNI - Aditya Yuda Negara; Elisabeth Tanti; Mohamad Rachmad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The implementation of Internal Control over Financial Reporting (ICFR/PIPK) is a vital foundation for Srenum TNI (General Policy and Planning Staff of the Indonesian National Armed Forces) to produce accurate financial information as a basis for strategic decision-making by the TNI Commander. This study aims to analyze the effectiveness of PIPK implementation at the Srenum TNI unit and identify the challenges faced in improving the quality of financial statements in accordance with government accounting standards. The research methodology employs a descriptive qualitative approach with a Control Self-Assessment (CSA) framework, as mandated by Minister of Finance Regulation (PMK) No. 17/2019. Data collection was conducted through technical triangulation, including: (1) Document Review of the five components of internal control; (2) Technical Interviews with treasury officials and SAKTI application operators; and (3) a Quantitative Survey involving 87 Srenum TNI personnel to measure perceptions of the control environment. The analysis focused on significant accounts—such as equipment, machinery, and inventory—through reperformance procedures within the SAKTI and SIMAK BMN applications. The results indicate that Srenum TNI has achieved